SOX9 mediates the phenotypic transformation of vascular smooth muscle cells in restenosis after carotid artery injury - Chuan Jiang; Chuan Jiang; Jiasen Ye; Jie Huang; Yang Gao; Hong Chen; Fuqiang Guo; Lei Guo; Xiaofan Yuan (Frontiers in Cell and Developmental Biology)
In-stent restenosis (ISR) remains a significant public health challenge globally, as millions of stents are implanted annually. Elucidating the mechanisms underlying ISR is essential for developing effective preventive and therapeutic strategies. In this study, we identified SOX9, a transcription factor, as a key factor involved in the pathogenesis of ISR. Morphological and histological analyses of human carotid atherosclerotic plaques revealed high expression of SOX9 at the interface between the fibrous cap (FC)—predominantly composed of α-smooth muscle actin (α-SMA)-positive vascular smooth muscle cells (VSMCs)—and the lipid-rich necrotic core (LRNC), enriched with CD68-positive macrophages. This region is characterized by a high frequency of phenotypic transformation of VSMCs. Using a carotid artery balloon injury model, we observed high expression of SOX9 in the neointima, and SOX9 knockdown significantly attenuated intimal hyperplasia. In vitro, SOX9 knockdown in primary VSMCs suppressed platelet-derived growth factor-BB (PDGF-BB)-induced phenotypic transformation, proliferation, and migration. Further studies using CUT&Tag analysis indicated that PDGF-BB promotes the AMPK signaling pathway, leading to the nuclear translocation of SOX9. A dual-luciferase reporter assay revealed that SOX9 directly binds to the motif of the signal transducer and activator of transcription 3 (STAT3) promoter, thereby enhancing the phenotypic transformation of VSMCs. This study uncovered a novel molecular mechanism in which AMPK-mediated SOX9 activation facilitates its interaction with STAT3 to regulate the transformation, proliferation, and migration of VSMCs. These findings suggest that targeting the SOX9–STAT3 axis can serve as a promising therapeutic strategy for the prevention and treatment of ISR.